Simultaneous Production of Multiple Antimicrobial Compounds by Bacillus velezensis ML122-2 Isolated From Assam Tea Leaf [Camellia sinensis var. assamica (J.W.Mast.) Kitam.] - Rungsirivanich, Patthanasak; Parlindungan, Elvina; O’Connor, Paula M.; Field, Des; Mahony, Jennifer; Thongwai, Narumol; van Sinderen, Douwe (Frontiers in Microbiology, 2021)
Bacillus velezensis ML122-2 is an antimicrobial-producing strain isolated from the leaf of Assam tea or Miang (Camellia sinensis var. assamica (J.W.Mast.) Kitam.). The cell-free supernatant (CFS) of strain ML122-2 exhibits a broad-spectrum antimicrobial activity against various Gram-positive and Gram-negative bacteria as well as the mold Penicillium expansum. The genome of B. velezensis ML122-2 was sequenced and in silico analysis identified three potential bacteriocin-associated gene clusters, i.e., those involved in the production of mersacidin, amylocyclicin and LCI. Furthermore, six gene clusters exhibiting homology (78-100% DNA sequence identity) to those associated with the secondary metabolites bacilysin, bacillibactin, surfactin, macrolactin H, bacillaene and plipastatin were identified. Individual antimicrobial activities produced by B. velezensis ML122-2 were purified and characterized by Matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry analysis, revealing three antimicrobial peptides with molecular masses corresponding to surfactin, plipastatin and amylocyclicin. Transcriptional analysis of specific genes associated with mersacidin (mrsA), amylocyclicin (acnA), plipastatin (ppsA) and surfactin (srfAA) production by B. velezensis ML122-2 showed that the first was not transcribed under the conditions tested, while the latter three were, consistent with the presence of the associated peptides as determined by mass spectrometry analysis. These findings demonstrate that B. velezensis ML122-2 has the genetic capacity to produce a wide range of antimicrobial activities that may support a specific community structure and highlight the biotechnological properties of Assam tea.